Simplifying algebraic expressions

Hi,

This is quite a basic query but I am having difficulty figuring out the following and would like some assistance.

(x+3)-(x+1)

= x+3-x-1

=2

I don't understand how we end up with = x+3-x-1

Could some please explain the steps taken to get here?

Many thanks

Re: Simplifying algebraic expressions

Quote:

Originally Posted by

**mrmorrison** Hi,

This is quite a basic query but I am having difficulty figuring out the following and would like some assistance.

(x+3)-(x+1)

= x+3-x-1

=2

I don't understand how we end up with = x+3-x-1

It's the "distributive law": a(b+ c)= ab+ ac. Here -1(x+ 1)= (-1)x+ (-1)(1)= -x- 1.

Quote:

Could some please explain the steps taken to get here?

Many thanks

Re: Simplifying algebraic expressions

Thanks for your help, this had made it much clearer!

Re: Simplifying algebraic expressions

I use to get so confused with expressions like this but its pretty simple actually :)

if you see -+ sign in between the two you should know you have to multiply them with the numbers inside the brackets.

(x+3) -(x+1)

(x+3) -1(x+1) there is a imaginary 1 after the negative value if you can see it like that.

x+3 -x-1

x+3-x-1

x-x=0

3-1=2

:)